Protection of Children in Conflict with Laws and Child Victims in the Diversion Implementation in Indonesia - Kurniawan, Yunan Prasetyo; Hartiwiningsih; Purwadi, Hari; Soehartono (International Journal of Psychosocial Rehabilitation, 2020)
Children today are at increased risk of becoming perpetrators or victims in the existence of crime. Too often, children are victims of theft, robbery, violence, sexual assault, harassment, intimidation and domestic violence, and an irony when they are also able to do so. Restorative justice through diversion is an alternative approach of justice that unites victims and perpetrators to find their own ways to recover damage, has much to offer young victims. But there are many risks in face-to-face meetings between child victims and older offenders. The human rights to child victims are those stated in the UN Convention on the Rights of the Child, the most consensual agreement ever received by the United Nations. The needs of child victims are based on many empirical studies and theories developed in the psycho-social literature. Children as perpetrators and victims have the right to remain protected and get good services and welfare in accordance with the mandate of the law, children as perpetrators of crime must get special services for children and welfare according to the children's field, including child victims. Child victims as a result of a crime often become neglected considering the difficulty of child victims to obtain the prescribed protection facilities stipulated in the positive law of children. The application of diversion in efforts to deal with children who are dealing with the law (children as perpetrators of crime) and children as victims (victims of criminal acts) is expected to be a novelty of child criminal problems. Thus, the state, society and individuals must make every effort to implement diversion in developing child protection efforts in various fields of life and livelihood in a country, community and family.